Creating the cultures of the future: cultural strategy, policy and institutions in Gramsci. Part one: Gramsci and cultural policy studies: some methodological reflections - Merli, Paola (Taylor & Francis, 2013)
Gramsci’s writings have rarely been discussed and used systematically by scholars in cultural policy studies, despite the fact that in cultural studies, from which the field emerged, Gramsci has been a major source of theoretical concepts. Cultural policy studies were, in fact, theorised as an anti-Gramscian project between the late 1980s and the early 1990s, when a group of scholars based in Australia advocated a major political and theoretical reorientation of cultural studies away from hegemony theory and radical politicisation, and towards reformist-technocratic engagement with the policy concerns of contemporary government and business. Their criticism of the ‘Gramscian tradition’ as inadequate for the study of cultural policy and institutions has remained largely unexamined in any detail for almost twenty years and seems to have had a significant role in the subsequent neglect of Gramsci’s contribution in this area of study. This essay, consisting of three parts, is an attempt to challenge such criticism and to provide an analysis of Gramsci’s writings, with the aim of proposing a more systematic contribution of his work to the theoretical development of cultural policy studies. In Part One, I question the use of the notion of ‘Gramscian tradition’ made by its critics and challenge the claim that it was inadequate for the study of cultural policy and institutions. In parts Two and Three, I consider Gramsci’s specific writings on questions of cultural strategy, policy and institutions, which have so far been overlooked by scholars, arguing that they provide further analytical insights to those offered by his more general concepts. More specifically, in Part Two, I consider Gramsci’s pre-prison writings and political practice in relation to questions of cultural strategy and institutions. I argue that the analysis of these early texts, which were written in the years in which Gramsci was active in party organisation and leadership, is fundamental not only for understanding the nature of Gramsci’s early and continued involvement with questions of cultural strategy and institutions, but also as a key for deciphering and interpreting cultural policy themes that he later developed in the prison notebooks, and which originated in earlier debates. Finally, in Part Three, I carry out a detailed analysis of Gramsci’s prison notes on questions of cultural strategy, policy and institutions, which enrich the theoretical underpinnings for critical frameworks of analysis as well as for radical practices of cultural strategy, cultural policy-making and cultural organisation. I then answer the question of whether Gramsci’s insights amount to a theory of cultural policy.